Aerogel with radio frequency dielectric near-zero performance and water evaporation performance as well as preparation method and application thereof
By preparing polyurethane/high entropy alloys @carbon, polyurethane/copper@carbon and polyurethane/cobalt nickel copper alloys @carbon aerogels, the problem of light weight of radio frequency dielectric near zero materials and difficult to achieve plasma resonance in RF frequency bands is solved, and The combination of radio frequency dielectric near-zero performance and water evaporation performance has promoted the development of multifunctional dielectric near-zero materials.
Patent Information
- Application Number
- CN202411328941.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing RF dielectric near zero materials are difficult to achieve light weight, cannot meet the light weight characteristics of electronic equipment integration, and plasma resonance in the RF frequency band is difficult to achieve, limiting the performance improvement of RF electronic devices.
Aerogels such as polyurethane/high entropy alloy @carbon, polyurethane/copper @carbon and polyurethane/cobalt nickel copper alloy @carbon were prepared through entropy engineering strategies to achieve the combination of radio frequency dielectric near-zero performance and water evaporation performance, and designed Lightweight aerogel.
It has achieved negative dielectric performance in the range of 1M Hz to 110M Hz, and achieved dielectric near zero performance near 24M Hz, showing good water evaporation performance and mechanical properties, promoting the development of multifunctional dielectric near zero materials .
Smart Images

Figure CN119192659A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of dielectric near-zero materials, and specifically to an aerogel having radio frequency dielectric near-zero performance and water evaporation performance, and a preparation method and application thereof. Background Art
[0002] Electromagnetic metamaterials have unique physical phenomena such as negative dielectric constant, negative magnetic permeability, dielectric near-zero or near-zero magnetic permeability, and exhibit novel physical properties such as negative refractive index and field enhancement effect. They have broad application prospects in electromagnetic shielding and absorption, optical nonlinearity, high-order harmonics, meta-lenses, etc. Dielectric near-zero materials, whose real part of dielectric constant often undergoes changes from positive to negative or from negative to positive, exhibit very low dielectric constants near the plasma frequency, which has attracted widespread attention from researchers. Due to the extremely low dielectric constant, dielectric near-zero materials usually exhibit unique physical properties such as a refractive index close to zero and a huge electric field near the plasma frequency, thus showing important applications in fields such as perfect absorption and nonlinear nanodevices. At present, there are two main methods to achieve dielectric near-zero materials. One is to continue the traditional metamaterial preparation process and achieve dielectric near-zero properties by constructing artificial periodic structures. The other is to construct a metal / dielectric dielectric stack (or plasma filler / dielectric dielectric composite material) based on the effective medium theory using the negative dielectric constant of metal or plasma filler and the positive dielectric constant of the medium to achieve dielectric near-zero performance. For common plasma materials such as silver, gold, carbon nanotubes, graphene and semiconductors, their plasma resonance frequencies are usually in the infrared, ultraviolet, visible light range, etc., so there is very little research on RF dielectric near-zero materials because plasma resonance in the RF frequency band is difficult to objectively achieve.
[0003] However, the research and development of RF dielectric near-zero materials is indeed of great significance and vital importance. Because with the integration, intelligence and miniaturization of electronic information technology, RF devices are increasingly becoming a bottleneck in the development of electronic information technology, and there is an urgent need to innovate and break through existing principles and technologies. In the terahertz frequency band, dielectric near-zero materials are combined with devices (such as photodetectors and antennas) to achieve performance breakthroughs. Therefore, combining RF dielectric near-zero materials with RF devices is an effective means to achieve performance breakthroughs in RF electronic devices.
[0004] At present, the realization of RF dielectric near-zero materials is mainly plasma filler / dielectric composite materials or ceramics. However, in order to be integrated with electronic devices, an important feature of RF dielectric near-zero materials is light weight. But these RF dielectric near-zero materials are difficult to meet this characteristic. Therefore, designing a lightweight RF dielectric near-zero material is inevitable and urgent. Summary of the invention
[0005] The purpose of the present invention is to provide an aerogel with radio frequency dielectric near-zero performance and water evaporation performance, and a preparation method and application thereof.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] An aerogel with radio frequency dielectric near-zero performance and water evaporation performance is any one of polyurethane / high entropy alloy@carbon aerogel, polyurethane / copper@carbon and polyurethane / cobalt-nickel-copper alloy@carbon aerogel.
[0008] The preparation method of the polyurethane / high entropy alloy@carbon aerogel comprises the following steps:
[0009] (1) Synthesis of high entropy alloy@carbon aerogel
[0010] First, 1,3,5-tricarboxylic acid was dissolved in a solution of ethanol and deionized water and stirred, which was labeled as solution A;
[0011] Ferric chloride hexahydrate, nickel chloride hexahydrate, cobalt chloride hexahydrate, manganese chloride, copper chloride dihydrate and collagen peptide protein were dissolved in deionized water, which was labeled as solution B;
[0012] Then, solution B was added to solution A and stirred to form high entropy metal organogel / collagen peptide; the high entropy metal organogel / collagen peptide was poured into a centrifuge tube and freeze-dried for 48 hours to obtain dry high entropy metal organogel / collagen peptide; the dried high entropy metal organogel / collagen peptide was annealed in a tubular furnace at 1000°C under argon protection at a heating rate of 10°C / min to obtain high entropy alloy@carbon aerogel;
[0013] (2) Preparation of polyurethane / high entropy alloy@carbon aerogel
[0014] Dissolving polyurethane in deionized water and stirring to obtain a polyurethane solution;
[0015] Then the high entropy alloy @ carbon aerogel was placed in a beaker, the polyurethane solution was poured into the beaker, and vacuum soaked at room temperature until there were no bubbles; the vacuum impregnation process was repeated until the polyurethane solution was completely immersed in the high entropy alloy @ carbon aerogel, and then taken out and stored at 50°C; after naturally cooling to room temperature, the polyurethane / high entropy alloy @ carbon aerogel was obtained.
[0016] Wherein, the preparation method of polyurethane / copper@carbon comprises the following steps:
[0017] (1) Synthesis of copper@carbon aerogel
[0018] First, 1,3,5-tricarboxylic acid was dissolved in a solution of ethanol and deionized water and stirred, which was marked as solution A;
[0019] Copper chloride dihydrate and collagen peptide protein were dissolved in deionized water, labeled as solution B;
[0020] Then, solution B was added to solution A and stirred to form metal organic gel / collagen peptide; the metal organic gel / collagen peptide was poured into a centrifuge tube and freeze-dried for 48 hours to obtain a dry metal organic gel / collagen peptide; the dried metal organic gel / collagen peptide was annealed in a tubular furnace at 1000°C under argon protection at a heating rate of 10°C / min to obtain copper@carbon aerogel;
[0021] (2) Preparation of polyurethane / copper@carbon aerogel
[0022] The polyurethane is dissolved in deionized water and stirred to obtain a polyurethane solution;
[0023] Then the copper@carbon aerogel was placed in a beaker, the polyurethane solution was poured into the beaker, and vacuum soaked at room temperature until there were no bubbles; the vacuum impregnation process was repeated until the polyurethane solution was completely immersed in the copper@carbon aerogel, and then taken out and stored at 50°C. After naturally cooling to room temperature, the polyurethane / copper@carbon aerogel was obtained.
[0024] The preparation method of the polyurethane / cobalt-nickel-copper alloy@carbon aerogel comprises the following steps:
[0025] (1) Synthesis of Cobalt-Nickel-Copper Alloy@Carbon Aerogel
[0026] First, 1,3,5-tricarboxylic acid was dissolved in a solution of ethanol and deionized water and stirred vigorously with ultrasound, which was labeled as solution A;
[0027] Nickel chloride hexahydrate, cobalt chloride hexahydrate, copper chloride dihydrate and collagen peptide protein were dissolved in deionized water, marked as solution B;
[0028] Then, solution B was added to solution A and stirred to form metal organic gel / collagen peptide; the metal organic gel / collagen peptide was poured into a centrifuge tube and freeze-dried for 48 hours to obtain a dry metal organic gel / collagen peptide; the dried metal organic gel / collagen peptide was annealed in a tubular furnace at 1000°C under argon protection at a heating rate of 10°C / min to obtain cobalt nickel copper alloy@carbon aerogel;
[0029] (2) Preparation of polyurethane / cobalt-nickel-copper alloy@carbon aerogel
[0030] Dissolve polyurethane in deionized water and mechanically stir for 30 minutes at room temperature to obtain a polyurethane solution;
[0031] Then the cobalt-nickel-copper alloy@carbon aerogel was placed in a beaker, the polyurethane solution was poured into the beaker, and vacuum soaked at room temperature until there were no bubbles; the vacuum impregnation process was repeated until the polyurethane solution was completely immersed in the cobalt-nickel-copper alloy@carbon aerogel, and then taken out and stored at 50°C. After naturally cooling to room temperature, the polyurethane / cobalt-nickel-copper alloy@carbon aerogel was obtained.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) This paper designs lightweight aerogels with radio frequency dielectric near-zero response for the first time and prepares polyurethane / high entropy alloy@carbon (PU / HEA@C) aerogels through entropy engineering strategy, opening up the development of advanced multifunctional dielectric near-zero response materials in the field of water evaporation.
[0034] (2) The present invention also prepares polyurethane / copper@carbon (PU / Cu@C) and polyurethane / cobalt-nickel-copper alloy@carbon (PU / CoNiCu@C) aerogels. Among them, polyurethane / copper@carbon aerogels and polyurethane / cobalt-nickel-copper alloy@carbon aerogels exhibit negative dielectric properties at 1 MHz to 110 MHz, while the dielectric constant of polyurethane / high entropy alloy@carbon aerogels turns from negative to positive, achieving near-zero dielectric properties at around 24 MHz.
[0035] (3) The aerogel prepared by the present invention exhibits good water evaporation performance, wherein the polyurethane / high entropy alloy@carbon aerogel achieves a rapid water evaporation rate of 3.21 kg·m under 1 sun radiation intensity. -2 ·h -1 . BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a real photo of high entropy alloy@carbon aerogel.
[0037] Figure 2 This is the SEM image of high entropy alloy@carbon aerogel.
[0038] Figure 3 TEM image of high entropy alloy@carbon aerogel and mapping distribution map of metal elements.
[0039] Figure 4 In the figure, (a) is the XRD pattern of high entropy alloy@carbon aerogel; (b) is the metal element ratio of high entropy alloy@carbon aerogel.
[0040] Figure 5 This is a real photo of polyurethane / high entropy alloy@carbon aerogel.
[0041] Figure 6 This is the SEM image of polyurethane / high entropy alloy@carbon aerogel.
[0042] Figure 7 This is the relationship between the real part of the dielectric constant of polyurethane / high entropy alloy@carbon aerogel and the frequency.
[0043] Figure 8 This is the stress-strain curve of polyurethane / high entropy alloy@carbon aerogel.
[0044] Fig. 9 In the figure, (a) is the SEM image of copper@carbon aerogel; (b) is the XRD image of copper@carbon aerogel.
[0045] Fig.10 This is the SEM image of polyurethane / copper@carbon aerogel.
[0046] Fig.11 This is the relationship between the real part of the dielectric constant of polyurethane / copper@carbon aerogel and the frequency.
[0047] Fig.12 In the figure, (a) is the SEM image of cobalt nickel copper @ carbon aerogel; (b) is the XRD image of cobalt nickel copper @ carbon aerogel.
[0048] Fig.13 This is the SEM image of polyurethane / cobalt-nickel-copper alloy@carbon aerogel.
[0049] Fig.14 This is the relationship between the real part of the dielectric constant of polyurethane / cobalt-nickel-copper alloy@carbon aerogel and the frequency.
[0050] Fig.15 In the figure, (a)-(c) are the wettability tests of polyurethane / copper@carbon aerogel, polyurethane / cobalt-nickel-copper alloy@carbon aerogel and polyurethane / high entropy alloy@carbon aerogel, respectively.
[0051] Fig.16 The absorption of light (250 nm-2500 nm wavelength) by polyurethane / copper@carbon aerogel, polyurethane / cobalt-nickel-copper alloy@carbon aerogel and polyurethane / high entropy alloy@carbon aerogel.
[0052] Fig.17 Water evaporation rate of polyurethane / copper@carbon aerogel, polyurethane / cobalt-nickel-copper alloy@carbon aerogel and polyurethane / high entropy alloy@carbon aerogel. DETAILED DESCRIPTION
[0053] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0054] Example 1
[0055] A method for preparing polyurethane / high entropy alloy@carbon (PU / HEA@C) aerogel, comprising the following specific steps:
[0056] (1) Synthesis of high entropy alloy@carbon (HEA@C) aerogel
[0057] First, 1,3,5-tricarboxylic acid (1 g) was dissolved in a solution of ethanol (10 mL) and deionized water (3 mL), and stirred vigorously with ultrasound, which was labeled as solution A.
[0058] Ferric chloride hexahydrate (1 mmol), nickel chloride hexahydrate (1 mmol), cobalt chloride hexahydrate (1 mmol), manganese chloride (1 mmol), copper chloride dihydrate (1 mmol) and collagen peptide protein (1 g) were dissolved in deionized water (30 mL), which was marked as solution B.
[0059] Then, solution B was added to solution A and stirred. After a few minutes, a high entropy metal organic gel / collagen peptide (HE-MOG / CP) was formed. The gel was poured into a centrifuge tube and freeze-dried for 48 hours to obtain dry HE-MOG / CP. The dried HE-MOG / CP was annealed in a tube furnace at 1000°C under argon protection at a heating rate of 10°C / min for 2 hours to obtain a high entropy alloy @ carbon (HEA@C) aerogel. The product photo is shown in the figure. Figure 1 shown.
[0060] Field emission scanning electron microscopy (Philips XL-30) was used to characterize the microstructure of the materials. Figure 2 a. Figure 2 b is the SEM image of high entropy alloy@carbon aerogel. It can be observed that many high entropy alloy particles are loaded on the carbon layer structure of the aerogel, and a porous structure is observed.
[0061] The morphology and element distribution of high entropy alloy@carbon aerogel were characterized by high-resolution transmission electron scanning microscopy (FEI Talos F200x). Figure 3 As shown in Figure 2, it can be observed that the particle size of the high entropy alloy is at the nanometer level, and the five metal elements of manganese, iron, cobalt, nickel and copper are evenly distributed.
[0062] Figure 4 a is the XRD pattern of high entropy alloy @ carbon aerogel. The diffraction peaks of crystal planes (111), (200), (220) and (311) are observed, which are consistent with the PDF card, proving that a single-phase high entropy alloy with a face-centered cubic structure is generated. The metal element ratio of high entropy alloy @ carbon aerogel was tested using an inductively coupled plasma atomic emission spectrometer (PE optima 6000). The results are shown in Figure 4As shown in b. Manganese accounts for 5.1% atomic ratio, iron accounts for 25.3% atomic ratio, cobalt accounts for 19.4% atomic ratio, nickel accounts for 27.4% atomic ratio, and copper accounts for 22.8% atomic ratio. High entropy alloy is defined as a single-phase alloy of multiple elements, in which each element accounts for 5-35%. The above test results meet this condition, proving that high entropy alloy nanoparticles have been successfully synthesized in carbon aerogel.
[0063] (2) Preparation of polyurethane / high entropy alloy@carbon (PU / HEA@C) aerogel
[0064] Dissolve polyurethane (20 ml) in deionized water (30 ml) and mechanically stir for 30 min at room temperature to obtain a polyurethane solution. Then put the HEA@C aerogel into a beaker, pour the polyurethane solution into the beaker, and soak it in vacuum at room temperature until there are no bubbles. Repeat the vacuum impregnation process until the polyurethane solution is completely immersed in the HEA@C aerogel, then take it out and store it at 50°C for 4 hours. After naturally cooling to room temperature, a polyurethane / high entropy alloy@carbon (PU / HEA@C) aerogel is obtained. The product photo is shown in the figure. Figure 5 As shown. It can be seen that even on a leaf, a large piece of aerogel can be carried, proving the lightweight nature of polyurethane / high entropy alloy@carbon aerogel.
[0065] Figure 6 This is the SEM image of polyurethane / high entropy alloy@carbon aerogel. A large number of porous structures can be observed, and from the polyurethane-carbon interface, it can be seen that the polyurethane is mainly attached to the surface of the carbon aerogel without destroying the porous carbon network structure of the carbon aerogel.
[0066] Figure 7 The relationship between the real part of the dielectric constant of polyurethane / high entropy alloy@carbon aerogel and the frequency is shown in the figure. The real part of the dielectric constant changes from negative to positive, and the dielectric constant is close to zero near 24 MHz, thus achieving near-zero RF dielectric performance.
[0067] Figure 8 The stress-strain curve of polyurethane / high entropy alloy @ carbon aerogel. Polyurethane / high entropy alloy @ carbon aerogel exhibits good mechanical properties, mechanical elasticity and compression properties. The mechanical properties of polyurethane / high entropy alloy @ carbon aerogel were comprehensively studied using a Mark-10 tester at room temperature. For compression evaluation, the samples were carefully arranged on the test surface and then compressed at a consistent and controlled rate of 30 mm / min to accurately measure their resistance to deformation under pressure. The aerogel can still return to its original shape after being compressed 100 times, and the stress-strain curve is the same as the initial one, showing excellent mechanical elasticity.
[0068] Example 2
[0069] A method for preparing a polyurethane / copper@carbon (PU / Cu@C) aerogel, comprising the following specific steps:
[0070] (1) Synthesis of copper@carbon (Cu@C) aerogel
[0071] First, 1,3,5-tricarboxylic acid (1 g) was dissolved in a solution of ethanol (10 mL) and deionized water (3 mL), and stirred vigorously with ultrasound, which was labeled as solution A.
[0072] Copper chloride dihydrate (5 mmol) and collagen peptide protein (1 g) were dissolved in deionized water (30 mL), which was labeled as solution B.
[0073] Then, solution B was added to solution A and stirred. After a few minutes, metal organic gel / collagen peptide (MOG / CP) was formed. The gel was poured into a centrifuge tube and freeze-dried for 48 hours to obtain dry MOG / CP. The dried MOG / CP was annealed in a tube furnace at 1000°C under argon protection at a heating rate of 10°C / min for 2 hours to obtain copper@carbon (Cu@C) aerogel.
[0074] Field emission scanning electron microscopy (Philips XL-30) was used to characterize the microstructure of the materials. Fig. 9 a is a SEM image of copper@carbon aerogel. It can be observed that a lot of copper metal particles are loaded on the carbon sheet structure of the aerogel, and a porous structure is observed. The phase structure of the material is characterized using an X-ray diffractometer (D / MaxB, Rigaku). Fig. 9 b is the XRD pattern of copper@carbon aerogel. Diffraction peaks of crystal planes (111), (200), (220) and (311) are observed, which are consistent with the PDF card, proving that single copper with a face-centered cubic structure is generated, but no metallic copper oxide is generated.
[0075] (2) Preparation of polyurethane / copper@carbon (PU / Cu@C) aerogel
[0076] Polyurethane (20 mL) was dissolved in deionized water (30 mL) and mechanically stirred at room temperature for 30 min to obtain a polyurethane solution. The Cu@C aerogel was then placed in a beaker, and the polyurethane solution was poured into the beaker and vacuum-impregnated at room temperature until there were no bubbles. The vacuum impregnation process was repeated until the polyurethane solution was completely immersed in the Cu@C aerogel, then taken out and stored at 50 ° C for 4 hours. After naturally cooling to room temperature, a polyurethane / copper@carbon (PU / Cu@C) aerogel was obtained.
[0077] Fig.10This is the SEM image of polyurethane / copper@carbon aerogel. A large number of porous structures can be observed, and from the polyurethane-carbon interface, it can be seen that the polyurethane is mainly attached to the surface of the carbon aerogel without destroying the porous carbon network structure of the carbon aerogel.
[0078] Fig.11 The figure shows the relationship between the real part of the dielectric constant of polyurethane / copper@carbon aerogel and the frequency. The real part of the dielectric constant of the material from 1 MHz to 110 MHz was tested using an impedance analyzer (Agilent 4294A). The polyurethane / copper@carbon aerogel has a negative dielectric constant within the test frequency, achieving negative dielectric properties.
[0079] Example 3
[0080] A method for preparing polyurethane / cobalt nickel copper alloy @ carbon (PU / CoNiCu@C) aerogel, the specific steps are:
[0081] (1) Synthesis of Cobalt Nickel Copper @ Carbon (CoNiCu@C) Aerogel
[0082] First, 1,3,5-tricarboxylic acid (1 g) was dissolved in a solution of ethanol (10 mL) and deionized water (3 mL), and stirred vigorously with ultrasound, which was labeled as solution A.
[0083] Nickel chloride hexahydrate (1.67 mmol), cobalt chloride hexahydrate (1.67 mmol), copper chloride dihydrate (1.67 mmol) and collagen peptide protein (1 g) were dissolved in deionized water (30 mL), which was marked as solution B.
[0084] Then, solution B was added to solution A and stirred. After a few minutes, metal organic gel / collagen peptide (MOG / CP) was formed. The gel was poured into a centrifuge tube and freeze-dried for 48 hours to obtain dry MOG / CP. The dried MOG / CP was annealed in a tube furnace at 1000°C under argon protection at a heating rate of 10°C / min for 2 hours to obtain cobalt nickel copper alloy @ carbon (CoNiCu@C) aerogel.
[0085] Field emission scanning electron microscopy (Philips XL-30) was used to characterize the microstructure of the materials. Fig.12 a is the SEM image of Co-Ni-Cu@C aerogel, and it can be observed that the carbon sheet structure of the aerogel is loaded with alloy particles. The phase structure of the material was characterized using an X-ray diffractometer (D / MaxB, Rigaku). Fig.12 b is the XRD pattern of Co-Ni-Cu@C aerogel. Diffraction peaks of crystal planes (111), (200), (220) and (311) are observed, which are consistent with the PDF card, proving that an alloy with a face-centered cubic structure is generated.
[0086] (2) Preparation of polyurethane / cobalt nickel copper alloy@carbon (PU / CoNiCu@C) aerogel
[0087] Polyurethane (20 mL) was dissolved in deionized water (30 mL) and mechanically stirred at room temperature for 30 min to obtain a polyurethane solution. The CoNiCu@C aerogel was then placed in a beaker, and the polyurethane solution was poured into the beaker and vacuum-soaked at room temperature until there were no bubbles. The vacuum impregnation process was repeated until the polyurethane solution was completely immersed in the CoNiCu@C aerogel, then taken out and stored at 50°C for 4 hours. After naturally cooling to room temperature, a polyurethane / cobalt nickel copper alloy@carbon (PU / CoNiCu@C) aerogel was obtained.
[0088] Fig.13 This is the SEM image of polyurethane / cobalt-nickel-copper alloy@carbon aerogel. A large number of porous structures can be observed, and from the polyurethane-carbon interface, it can be seen that the polyurethane is mainly attached to the surface of the carbon aerogel without destroying the porous carbon network structure of the carbon aerogel.
[0089] Fig.14 The relationship between the real part of the dielectric constant of polyurethane / cobalt-nickel-copper alloy@carbon aerogel and the frequency is shown in the figure. The dielectric constant is negative within the test frequency, achieving negative dielectric properties.
[0090] Fig.15 In the figure, (a)-(c) are the wettability tests of polyurethane / copper@carbon aerogel, polyurethane / cobalt-nickel-copper alloy@carbon aerogel and polyurethane / high entropy alloy@carbon aerogel respectively. At room temperature, the wettability of the samples was evaluated using a contact angle meter (Krüss DSA100), ensuring that the relative humidity was about 60%. As can be seen from the figure, when water drops fell on the aerogel, the water droplets were immediately absorbed, indicating that all three aerogels have good hydrophilicity, which is conducive to water evaporation.
[0091] Fig.16 The absorption of light (250 nm-2500 nm wavelength) by polyurethane / copper@carbon aerogel, polyurethane / cobalt-nickel-copper alloy@carbon aerogel and polyurethane / high entropy alloy@carbon aerogel. The absorption spectra were obtained using a UV-visible-near infrared spectrometer (Solidspec-3700). The absorption of light by polyurethane / copper@carbon aerogel reached more than 92% in the full spectrum band (250 nm-2500 nm wavelength). The absorption of light by polyurethane / cobalt-nickel-copper alloy@carbon aerogel reached more than 94% in the full spectrum band (250 nm-2500 nm wavelength). The absorption of light by polyurethane / high entropy alloy@carbon aerogel reached more than 95% in the full spectrum band (250 nm-2500 nm wavelength).
[0092] Fig.17The water evaporation rate of polyurethane / copper@carbon aerogel, polyurethane / cobalt-nickel-copper alloy@carbon aerogel and polyurethane / high entropy alloy@carbon aerogel. In terms of water evaporation performance, a solar simulator (94043A, Newport) with an air mass 1.5G filter was used as the light source. The light intensity was set to 1 sun radiation intensity, and an electronic balance was used to continuously monitor the change in water mass. The evaporation evaluation was carried out under controlled conditions of a temperature of 24.5±1°C and a humidity of 60%. The aerogel samples were cut into discs with a diameter of 1 cm and a thickness of 0.2 cm. The water evaporation rate of polyurethane / copper@carbon aerogel is 2.85 kg·m -2 ·h -1 The water evaporation rate of polyurethane / cobalt-nickel-copper alloy@carbon aerogel is 3.04 kg·m -2 ·h -1 The water evaporation rate of polyurethane / high entropy alloy@carbon aerogel is 3.21 kg·m -2 ·h -1 .
[0093] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An aerogel having near-zero radio frequency dielectric performance and water evaporation performance, characterized in that: It is any one of polyurethane / high entropy alloy@carbon aerogel, polyurethane / copper@carbon and polyurethane / cobalt-nickel-copper alloy@carbon aerogel.
2. The method for preparing the aerogel having radio frequency dielectric near-zero performance and water evaporation performance according to claim 1, characterized in that: The preparation method of the polyurethane / high entropy alloy@carbon aerogel comprises the following steps: (1) Synthesis of high entropy alloy@carbon aerogel First, 1,3,5-tricarboxylic acid was dissolved in a solution of ethanol and deionized water and stirred, which was labeled as solution A; Ferric chloride hexahydrate, nickel chloride hexahydrate, cobalt chloride hexahydrate, manganese chloride, copper chloride dihydrate and collagen peptide protein were dissolved in deionized water, which was labeled as solution B; Then, solution B was added to solution A and stirred to form high entropy metal organogel / collagen peptide; the high entropy metal organogel / collagen peptide was poured into a centrifuge tube and freeze-dried for 48 hours to obtain dry high entropy metal organogel / collagen peptide; the dried high entropy metal organogel / collagen peptide was annealed in a tubular furnace at 1000°C under argon protection at a heating rate of 10°C / min to obtain high entropy alloy@carbon aerogel; (2) Preparation of polyurethane / high entropy alloy@carbon aerogel.
3. The method for preparing the aerogel having radio frequency dielectric near-zero performance and water evaporation performance according to claim 2, characterized in that: The step (2) in the preparation method of the polyurethane / high entropy alloy@carbon aerogel is specifically as follows: dissolving the polyurethane in deionized water and stirring to obtain a polyurethane solution; Then the high entropy alloy @ carbon aerogel was placed in a beaker, the polyurethane solution was poured into the beaker, and vacuum soaked at room temperature until there were no bubbles; the vacuum impregnation process was repeated until the polyurethane solution was completely immersed in the high entropy alloy @ carbon aerogel, and then taken out and stored at 50°C; after naturally cooling to room temperature, the polyurethane / high entropy alloy @ carbon aerogel was obtained.
4. The method for preparing the aerogel having radio frequency dielectric near-zero performance and water evaporation performance according to claim 1, characterized in that: The preparation method of the polyurethane / copper@carbon comprises the following steps: (1) Synthesis of copper@carbon aerogel First, 1,3,5-tricarboxylic acid was dissolved in a solution of ethanol and deionized water and stirred, which was marked as solution A; Copper chloride dihydrate and collagen peptide protein were dissolved in deionized water, labeled as solution B; Then, solution B was added to solution A and stirred to form metal organic gel / collagen peptide; the metal organic gel / collagen peptide was poured into a centrifuge tube and freeze-dried for 48 hours to obtain a dry metal organic gel / collagen peptide; the dried metal organic gel / collagen peptide was annealed in a tubular furnace at 1000°C under argon protection at a heating rate of 10°C / min to obtain copper@carbon aerogel; (2) Preparation of polyurethane / copper@carbon aerogel.
5. The method for preparing the aerogel having radio frequency dielectric near-zero performance and water evaporation performance according to claim 4, characterized in that: The step (2) in the preparation method of the polyurethane / copper@carbon aerogel is specifically as follows: dissolving polyurethane in deionized water and stirring to obtain a polyurethane solution; Then the copper@carbon aerogel was placed in a beaker, the polyurethane solution was poured into the beaker, and vacuum soaked at room temperature until there were no bubbles; the vacuum impregnation process was repeated until the polyurethane solution was completely immersed in the copper@carbon aerogel, and then taken out and stored at 50°C. After naturally cooling to room temperature, the polyurethane / copper@carbon aerogel was obtained.
6. The method for preparing the aerogel having radio frequency dielectric near-zero performance and water evaporation performance according to claim 1, characterized in that: The preparation method of the polyurethane / cobalt-nickel-copper alloy@carbon aerogel comprises the following steps: (1) Synthesis of Cobalt-Nickel-Copper Alloy@Carbon Aerogel First, 1,3,5-tricarboxylic acid was dissolved in a solution of ethanol and deionized water and stirred vigorously with ultrasound, which was labeled as solution A; Nickel chloride hexahydrate, cobalt chloride hexahydrate, copper chloride dihydrate and collagen peptide protein were dissolved in deionized water, marked as solution B; Then, solution B was added to solution A and stirred to form metal organic gel / collagen peptide; the metal organic gel / collagen peptide was poured into a centrifuge tube and freeze-dried for 48 hours to obtain a dry metal organic gel / collagen peptide; the dried metal organic gel / collagen peptide was annealed in a tubular furnace at 1000°C under argon protection at a heating rate of 10°C / min to obtain cobalt nickel copper alloy@carbon aerogel; (2) Preparation of polyurethane / cobalt-nickel-copper alloy@carbon aerogel.
7. The method for preparing aerogel having radio frequency dielectric near-zero performance and water evaporation performance according to claim 6, characterized in that: The step (2) in the preparation method of the polyurethane / cobalt-nickel-copper alloy@carbon aerogel is specifically as follows: dissolving the polyurethane in deionized water, and mechanically stirring at room temperature for 30 minutes to obtain a polyurethane solution; Then the cobalt-nickel-copper alloy@carbon aerogel was placed in a beaker, the polyurethane solution was poured into the beaker, and vacuum soaked at room temperature until there were no bubbles; the vacuum impregnation process was repeated until the polyurethane solution was completely immersed in the cobalt-nickel-copper alloy@carbon aerogel, and then taken out and stored at 50°C. After naturally cooling to room temperature, the polyurethane / cobalt-nickel-copper alloy@carbon aerogel was obtained.
8. Use of the aerogel having radio frequency dielectric near-zero performance and water evaporation performance as claimed in claim 1 in radio frequency electronic devices.
